2004
DOI: 10.1111/j.1360-0443.2004.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of personality disorder in alcohol and drug services and associated comorbidity

Abstract: In both alcohol and drug service populations, personality disorder is associated with significantly increased rates of psychopathology and social morbidity that worsens with increasing severity of the disorder. Despite this, personality disorder is poorly identified by clinical staff. The PAS-Q may be useful as a clinical assessment tool in the substance misuse population for the early identification and management of patients with personality disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 34 publications
3
42
1
Order By: Relevance
“…The prevalence of PD in our study was, however, lower than in most other studies [4,6,13] . There may be several reasons for this difference.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The prevalence of PD in our study was, however, lower than in most other studies [4,6,13] . There may be several reasons for this difference.…”
Section: Discussioncontrasting
confidence: 54%
“…Other psychiatric disorders and socioeconomic problems along with PD often occur among alcoholics [5,6] , and patients suffering from PD have additional symptoms and problems compared with patients who only suffer from alcohol abuse [6,7] . Some studies describing the effect of PD on alcohol treatment have found that patients with PD (A+PD) derive reduced benefit from the therapy and increased risk of relapse [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the risk factors for suicidal behavior, an association of CCPD with depression (Russel, Kornstein, Shea et al, 2003) as well as alcohol (Bowden-Jones, Iqbal, Tyrer et al, 2004) and substance use (Skinstad & Swain, 2001) has been reported. Furthermore, CCPD has been reported to be associated with anger/hostility (Fava, 1998;Gould, Ball, Kaspi et al, 1996), another risk factor for suicidal behavior (Mann, Waternaux, Haas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of suicidal behavior in CCPD subjects cited above, co-morbidity of other PDs, which could affect the association of CCPD with suicidal behavior, was not excluded. To our knowledge, only one psychological autopsy study excluded co-morbidity of other PD, and reported that "pure" CCPD was an independent predictor for completed suicide only for men (Schneider, Watterling, Sargk et al, 2005).With regard to the risk factors for suicidal behavior, an association of CCPD with depression (Russel, Kornstein, Shea et al, 2003) as well as alcohol (Bowden-Jones, Iqbal, Tyrer et al, 2004) and substance use (Skinstad & Swain, 2001) has been reported. Furthermore, CCPD has been reported to be associated with anger/hostility (Fava, 1998;Gould, Ball, Kaspi et al, 1996), another risk factor for suicidal behavior (Mann, Waternaux, Haas et al, 1999).…”
mentioning
confidence: 99%
“…The benefit of these drugs is unlikely to be a direct consequence of their antidepressant effect, although it could be connected -a similar study of fluoxetine in patients with depression and alcoholism showed improvement in both depression and drinking behaviour compared with placebo (Cornelius et al, 1997). Although personality disorder was not measured in this study, it is likely that a substantial proportion -about 50%, from prevalence figures in this clinical population (Bowden-Jones et al, 2004) -had this condition.…”
Section: Tricyclic Antidepressants and Selective Serotonin Reuptake Imentioning
confidence: 99%